2007
DOI: 10.1227/01.neu.0000280002.41696.d8
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Window of Metabolic Brain Vulnerability to Concussions

Abstract: OBJECTIVE:In the present study, we investigate the existence of a temporal window of brain vulnerability in rats undergoing repeat mild traumatic brain injury (mTBI) delivered at increasing time intervals. METHODS: Rats were subjected to two diffuse mTBIs (450 g/1 m height) with the second mTBI delivered after 1 (n ϭ 6), 2 (n ϭ 6), 3 (n ϭ 6), 4 (n ϭ 6), and 5 days (n ϭ 6) and sacrificed 48 hours after the last impact. Sham-operated animals were used as controls (n ϭ 6). Two further groups of six rats each rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

10
213
1
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 268 publications
(226 citation statements)
references
References 55 publications
10
213
1
2
Order By: Relevance
“…These experimental results have recently been confirmed 32 and strongly corroborate the finding reported in the present study, indicating temporary decrease in NAA and Cr levels and no change in Cho levels in our cohort of athletes with postconcussive head injury. Other authors indicated that patients suffering from mTBI underwent transient increase in Cr levels in the white matter and no change in NAA levels, 28,29 in contrast to the results of the present and previous studies 16,26,27,33,34 and also to a conspicuous number of preclinical studies demonstrating temporary decrease in NAA 8,10,11,21 and Cr pool following mTBI. 31,32 To explain their results, these authors concluded that an increase in total Cr (Cr and CrP) levels in the white matter may support a larger pool of high-energy phosphates (CrP and ATP), helping to restore mTBI-induced alteration of cell homeostasis through upregulation of membrane pumps and other processes of cellular repair.…”
Section: Discussioncontrasting
confidence: 85%
See 4 more Smart Citations
“…These experimental results have recently been confirmed 32 and strongly corroborate the finding reported in the present study, indicating temporary decrease in NAA and Cr levels and no change in Cho levels in our cohort of athletes with postconcussive head injury. Other authors indicated that patients suffering from mTBI underwent transient increase in Cr levels in the white matter and no change in NAA levels, 28,29 in contrast to the results of the present and previous studies 16,26,27,33,34 and also to a conspicuous number of preclinical studies demonstrating temporary decrease in NAA 8,10,11,21 and Cr pool following mTBI. 31,32 To explain their results, these authors concluded that an increase in total Cr (Cr and CrP) levels in the white matter may support a larger pool of high-energy phosphates (CrP and ATP), helping to restore mTBI-induced alteration of cell homeostasis through upregulation of membrane pumps and other processes of cellular repair.…”
Section: Discussioncontrasting
confidence: 85%
“…3,4 Such a cascade of molecular events is considered as the determinant of the so-called state of metabolic brain vulnerability, 5,6 which transiently exposes cerebral tissue to the cumulative effect of a second mTBI occurring during this particular period. 7,8 High-energy phosphates, 9,10 coenzyme A metabolites, 11 ATP catabolites, 11 and neurotransmitters, 12,13 are some of the substances whose concentrations are temporarily affected as a result of a traumatic insult. Of particular relevance is the finding that N-acetylaspartate (NAA), an abundant brain-specific compound involved in several relevant biological functions including water homeostasis 14 and lipid myelin biosynthesis, 15 clearly mirrors TBI-induced changes in ATP, showing the same pattern of decrease and recovery following mTBI and no recovery in severe TBI or repeat mTBIs.…”
mentioning
confidence: 99%
See 3 more Smart Citations